Answer :

guskarose

Answer E.

Explanation:

If A = (x₁, y₁) and B = (x₂, y₂):

d = √((x₂ - x₁)² + (y₂ - y₁)²)

A = (5, 6)

x₁ = 5, y₁ = 6

B = (-3. 2)

x₂ = -3, y₂ = 2

d = √((-3 - 5)² + (2 - 6)²)

d = √((-8)² + (-4)²)

d = √(64 + 16)

d = √80

Hi there!

We know our standard distance formula, [tex]\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}=d[/tex]. This is derived from the Pythagorean's theorem, as we can imagine there being a right triangle and finding the hypotenuse for the distance (See the attached graph).

Plugging these points in, we get:

[tex]\sqrt{(-3-5)^2+(2-6)^2}=d[/tex]

[tex]\sqrt{(-8)^2+(-4)^2}=d[/tex]

[tex]\sqrt{64+16}=d[/tex]

[tex]\sqrt{80}=d[/tex]

Thus, we know the answer is E, the square root of 80.

Hope this helps!

${teks-lihat-gambar} AprilKitties

Other Questions